2016
DOI: 10.5812/hepatmon.34202
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis E Virus Genotype 1 Among Blood Donors From Southwest of Iran

Abstract: BackgroundInfection with hepatitis E virus (HEV) is endemic in developing countries and reveals significant regional differences. Several studies have reported virus transmission via blood transfusion. To date, however, no cases of HEV RNA detection in blood donors have been reported from Iran.ObjectivesThe aim of this study was to determine the presence of HEV RNA in plasma samples of blood donors referred to a blood transfusion center in Shiraz in the southwest of Iran. The HEV genotypes were also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Our genotyping result goes in parallel with several studies identifying HEV genotype 1 infection among blood donors. Parsa et al have reported HEV RNA positivity in 12% (7 of 50) antibody‐positive samples and sequence analysis of these seven isolates revealed >80% similarity with genotype 1 in blood donors of Iran. Similarly, Zhang et al have reported that the majority of HEV infections in RNA‐positive donors in China were attributed to genotype 1 (19/33 = 58%) and genotype 4 (14/33 = 42%).…”
Section: Discussionmentioning
confidence: 98%
“…Our genotyping result goes in parallel with several studies identifying HEV genotype 1 infection among blood donors. Parsa et al have reported HEV RNA positivity in 12% (7 of 50) antibody‐positive samples and sequence analysis of these seven isolates revealed >80% similarity with genotype 1 in blood donors of Iran. Similarly, Zhang et al have reported that the majority of HEV infections in RNA‐positive donors in China were attributed to genotype 1 (19/33 = 58%) and genotype 4 (14/33 = 42%).…”
Section: Discussionmentioning
confidence: 98%
“…Out of these 50 HEV antibody‐positive samples, HEV RNA was detected in only 7 (12%), the majority of which were IgM‐positive. Sequence analysis of these 7 HEV RNA‐positive samples showed that blood donors were infected with HEV‐1 . The importance of this study stems from the reporting of high incidence rate of HEV RNA among blood donors, as well as the identification of HEV‐1, which is recognized as the most pathogenic genotype, especially among pregnant women .…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…As expected, and as previously documented in other parts of the world, seroprevalence of HEV increased with age, but exposure seemed to occur in early ages. In a recent study conducted in Southwest Iran in 2016, 50 out of 700 (7.1%) donated blood samples tested positive for HEV antibodies . Out of these 50 HEV antibody‐positive samples, HEV RNA was detected in only 7 (12%), the majority of which were IgM‐positive.…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…Responsible agencies should consider HEV screening in blood transfusions to avoid its infection and complications, especially in endemic areas where a higher risk is present, considering that every effort to minimize the potential of the transfusion-transmitted disease is valuable (31,33,34).…”
Section: Discussionmentioning
confidence: 99%